Influence of Feeder Design on Physiological and Haemato-Biochemical Parameters of Osmanabadi Goat Kids - Kankarwal, Gaurav; Pathak, Rupal; Dhirendra Bhonsle; Singh, Nishma; Bhagat, Vandana; Doneria, Raina; Parmar, Mehtab S (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
The effect of feeder design on the health and growth performance of the Osmanabadi goat kids was evaluated. A total of 18 Osmanabadi weaned kids of 5-6 month of age were randomly divided into 3 treatment group (n=6) viz T1, T2 and T3 groups for the study period of 60 days. T1 group kids were kept on conventional feeder and served as control, T2 on circular feeder and T3 on linear feeder. Rectal temperature, heart rate and respiration rate differed non-significantly across all the groups throughout the study. T3 group exhibited a significantly higher haemoglobin value (g/dl) than T2 followed by T1 group on 60th day. The PCV value ranged from 19.0±0.73 to 25.0±0.4. A statistically significant elevation in TEC was registered on the 60th day in T3 (14.8±0.03) and T2 (14.7±0.04) as compared to T1 (14.4±0.08). The T1 and T2 showed a substantial but non-significant increase in N/L ratio as compared to T3. The maximum mean protein level differed non-significantly and was found highest on the 60th day of experiment in T3 (6.8 ± 0.9) group. The glucose data indicated no significant difference among all the groups with the lowest value observed on the 60th day in T3 group. Our findings indicated that modified linear feeder design was more suitable and exerted minimal stress resulting in better health and welfare of kids.